Admission is not Always Necessary for Patients with Community-Acquired Pneumonia in Risk Classes IV and V Diagnosed in the Emergency Room - TJ Marrie; JQ Huang (Canadian Respiratory Journal)
OBJECTIVE: To determine the factors that allow patients with community-acquired pneumonia who are at high risk of mortality (risk classes IV and V) to be treated at home.